First-principles analysis of a molecular piezoelectric meta-nitroaniline. Issue 30 (9th May 2018) - Wang, Fu; Dai, Zelin; Gu, Yu; Cheng, Xiaomeng; Jiang, Yadong; Ouyang, Fangping; Xu, Jimmy; Xu, Xiangdong
Abstract : The piezoelectric and elastic properties of a molecular piezoelectric meta -nitroaniline (mNA) in its single-crystal form were investigated in the framework of first-principles density functional perturbation theory (DFPT). Abstract : The piezoelectric and elastic properties of a molecular piezoelectric meta -nitroaniline (mNA) in its single-crystal form were investigated in the framework of first-principles density functional perturbation theory (DFPT). Results support the recent experimental findings those despite being soft and flexible, mNA's piezoelectric coefficients are an order of magnitude greater than that of ZnO and LiNbO3 . A molecular-level insight into the piezoelectric properties of mNA is provided. These results are helpful not only for better understanding mNA, but also for developing new piezoelectric materials.